A small state's foreign affairs strategy: Making sense of Malaysia's strategic response to the South China Sea debacle. Issue 5 (20th October 2017) - Wey, Adam Leong Kok
ABSTRACT: Malaysia, being a small state in its asymmetrical relations with both the United States and China, is caught in a difficult position in the ongoing South China Sea debacle. Malaysia has been courted by both of these powerful states to be an influential regional facilitator to advance each of their respective strategic interests in the region. Malaysia's response thus far has been both cautious and enigmatic. This article traces Malaysia's foreign affairs strategic history during some of the most precarious days of the Cold War to explain its contemporary strategic choices and logic in the midst of great-power rivalries in the Southeast Asia region. The dual practice of selective alignment and strategic ambiguity by Malaysia, used effectively during the Cold War, continues to drive its foreign relations today and makes perfect strategic sense.